A review of fenfluramine for the treatment of Dravet syndrome patients - Kayla Simon; Hunter Sheckley; Christopher L. Anderson; Zhao Liu; Paul R. Carney (Elsevier, 2022)
Introduction: Dravet Syndrome (DS) is a rare epileptiform disorder typically presenting within the first year of life of a normally developing infant. It is characterized by several prolonged seizures that are often resistant to current anti-epileptic drug (AED) regimens. This paper outlines the history and clinical trials of the drug fenfluramine, a drug that when used in addition to AED regimens may provide hope to children affected by DS. Body: Fenfluramine (3-trifulormethyl-N-ethylamphetamine) is an amphetamine derivative that primarily affects serotonin neurotransmitter levels. It was initially prescribed in the 1960s as an appetite suppressant marketed as a weight loss drug. However, it was removed from the markets due to its association with cardiac valvopathies. It continued to by studied in epilepsy by Gastaut in the 1980s in children with self-induced syncope and irretractable epilepsy. In 2012, Ceulemans et al. studied the use of fenfluramine in patients with DS. Following the success of that retrospective case study, Nabbout et al. and Legae et al. conducted two randomized control trials leading to the FDA approval of fenfluramine under its trade name Fintepla in 2020. Discussion: The success of the randomized control trials suggests the addition of fenfluramine to current AED regimens may lead to better control of seizures in patients with DS. The side effects of fenfluramine prove to be manageable and the concern for valvopathies has not been reproducible with low dose fenfluramine.